Twenty-first century quantum mechanics : Hilbert Space to quantum computers : mathematical methods and conceptual foundations /: Hilbert Space to quantum computers : mathematical methods and conceptual foundations. (2017) - Fano, Guido; Blinder, S. M, 1932-
No abstract available